Analisis Sistem Pemberian Insentif Dalam Meningkatkan Kinerja Karyawan Pada PT. Berbinar Insightful Indonesia - Neneng Musyrifatul Amelia; Chintya Anggun Lestari; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out and analyze the provision of incentives to improve employee performance in service companies operating in the field of psychology. This research is included in qualitative research with a descriptive approach. The data used are primary and secondary data obtained from observations and interviews. Data analysis uses data transcription, source triangulation, and data reduction. The research results show that providing incentives to employees has both positive and negative impacts. The positive impact of providing incentives is increasing motivation, performance and increasing employee enthusiasm. Providing incentives also has negative impacts, including unfairness in providing incentives and decreasing employee work ethic.